Retail Policy Dilemma and The Existence of Modern Retail in Indonesia and Malaysia - Aan Sugiharto; Shannaz Mutiara Deniar (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research originated from the phenomenon of the rapid development of the modern retail industry, which can be found in big cities in Southeast Asian countries such as Indonesia and Malaysia. This phenomenon also coincides with the increasing level of public welfare and education, especially in urban areas. This phenomenon has resulted in an increasing number of modern retail stores which have a direct impact on the existence of traditional retail owned by the local community. The response then came from both the government and the retail industry itself. The government seems to be trying to make the development of the modern retail industry with its large capital power grow into a new force that threatens traditional retail, although, in the end, the traditional retail store owners themselves have to think of strategies to be able to continue to compete. The aim of this research is to compare the Indonesian and Malaysian government policies in retail industry regulation. The results of this study are that both countries issued mutually beneficial policies given the modern presence needed for labor needs, while the existence of traditional retailers must be maintained as one of the pillars of the country's economy in the informal sector. Policies for monitoring operating hours, building area, zoning, and guaranteeing labor absorption for modern retailers issued by the two countries with the aim of protecting the existence of traditional retailers that cannot compete directly in the capital.